2020
DOI: 10.1186/s12866-020-01816-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut microbiota in infants is associated with respiratory syncytial virus disease severity

Abstract: Background: Respiratory syncytial virus (RSV) is the number one cause of lower respiratory tract infections in infants. There are still no vaccines or specific antiviral therapies against RSV, mainly due to the inadequate understanding of RSV pathogenesis. Recent data suggest a role for gut microbiota community structure in determining RSV disease severity. Our objective was to determine the gut microbial profile associated with severe RSV patients, which could be used to help identify at-risk patients and dev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 45 publications
6
28
0
Order By: Relevance
“…Consistently, this likeness reinforces the finding of certain bacterial genera (e.g., Bacteroides ) potentially affecting the bronchiolitis course in our infants. The present study’s results are also reminiscent of those from a very recent investigation that showed an altered gut microbiota to be associated with RSV disease severity ( Harding et al., 2020 ). However, restricting our study to a single sample from each enrolled infant hindered us from providing any statistical inference or causality of the fecal bacterial composition with the illness severity as well as from investigating the differences in bacterial composition at the species level or in bacterial functionality between bronchiolitis infants’ groups.…”
Section: Discussionsupporting
confidence: 84%
“…Consistently, this likeness reinforces the finding of certain bacterial genera (e.g., Bacteroides ) potentially affecting the bronchiolitis course in our infants. The present study’s results are also reminiscent of those from a very recent investigation that showed an altered gut microbiota to be associated with RSV disease severity ( Harding et al., 2020 ). However, restricting our study to a single sample from each enrolled infant hindered us from providing any statistical inference or causality of the fecal bacterial composition with the illness severity as well as from investigating the differences in bacterial composition at the species level or in bacterial functionality between bronchiolitis infants’ groups.…”
Section: Discussionsupporting
confidence: 84%
“…Research into respiratory syncytial virus of infants, a key cause of LRTI, has shown an altered microbial community to be associated with severe disease symptoms (84) . A recent review by Enaud et al (85) documented current knowledge about the gut-lung axis.…”
Section: Aspects Of Gut Microbiota Modulation Related To Respiratory Infection and Covid-19mentioning
confidence: 99%
“…Harding et al. investigated stool samples collected by 95 babies, 37 healthy and 53 RSV-positive infants hospitalized (moderate RSV-disease) and 5 RSV-positive infants transferred to the pediatrician intensive care unit (ICU) (Severe RSV-disease) ( 89 ). All stool samples were collected within 72 hours of admission to analyze gut microbiota.…”
Section: Early-life Gut Microbiome Composition In Health and Diseasesmentioning
confidence: 99%
“…In the infants with severe RSV-disease group, the authors observed slightly lower alpha diversity, representing the richness and evenness of the bacterial community compared with moderate RSV-disease and healthy controls. While this study has limitations since it cannot determine if the changes are the cause or the consequence of the infection, the timing of the sample collection (72 hours post-hospitalization) could indicate that early-life gut microbiome composition correlates with RSV-disease severity ( 89 ). Considering the hypothesis of the gut-lung axis, it is reasonable that gut dysbiosis affects disease severity in patients with RSV infection.…”
Section: Early-life Gut Microbiome Composition In Health and Diseasesmentioning
confidence: 99%